Внесок Б.Д. Грінченка у вироблення наукових засад вивчення українських діалектів - Глуховцева, К.Д. (Лексикографічний бюлетень, 2014)
In this article, the ethnographic materials and «Dictionary of Ukrainian Language » by B. D. Grinchenko are researched from the point of view of this scientist who developed the scientifi c grounds for studying the Ukrainian dialects. It is proved that the scientifi c activity of B. D. Grinchenko falls on the intensive development period of the Ukrainian dialectology. Th us, the famous linguist synthesized the achievements of his precursors not occasionally. Continuing the tradition of Ukrainian linguists concerning the dialectological evidences, he consolidated the scientifi c grounds of writing the folkloric, ethnographic and dialectal materials. Th e principles of presenting the practical material in the lexicographical sources, which are actual nowadays, are implemented in practice by the scientist.